Circulating osteogenic endothelial progenitor cell counts: new biomarker for the severity of coronary artery disease. (15th January 2017) - Yang, Shi-Wei; Hennessy, Rebecca R.; Khosla, Sundeep; Lennon, Ryan; Loeffler, Darrell; Sun, Tao; Liu, Zhi; Park, Kyoung-Ha; Wang, Fei-Long; Lerman, Lilach O.; Lerman, Amir
Abstract: Background: There is increasing evidence implying that the early and functionally highly active circulating endothelial progenitor cell (CEPC) phenotype (CD34 −/CD133 +/KDR +) with osteogenic potential (OCN +) might link between vascular atherosclerotic calcification and mechanisms of bone metabolism. We sought to evaluate the early OCN + CEPC counts as an independent biomarker for the severity of coronary artery disease (CAD). Methods: Peripheral blood samples were drawn from 593 patients undergoing clinically indicated coronary angiography. CAD severity was assessed by the presence of significant coronary artery stenosis (CAS) as well as an ordinal categorical variable. Subjects were followed for all-cause death over a median follow-up of 40 months. Results: OCN + early CEPC counts (square-root transformed) were independently associated with the presence of significant CAS [odds ratio (OR) per standard deviation (SD) increment: 1.389, 95% confidence interval [CI]: 1.131 to 1.707, p = 0.002). Similar association was observed with an increase in levels of CAS (OR: 1.353, 95% CI: 1.157 to 1.582, p < 0.001). There was a weak tendency between OCN + early CEPC counts and all-cause mortality (p = 0.090), whereas the highest decile of OCN + early CEPC counts had a 2.991-fold increased risk of all-cause death (p = 0.047). Conclusions: We demonstrate for the first time an independent, significant, and strong correlation between OCN + early CEPC counts and CAD severity. Additionally, very high numbers of OCN + early CEPC tend to be linked to the risk of all-cause mortality. Highlights: We demonstrate for the first time an independent, significant, and strong correlation between the early and functionally highly active circulating endothelial progenitor cell phenotype (CD34- /CD133+ /KDR+) with osteogenic potential (OCN+) counts and the severity of coronary artery disease. Additionally, very high numbers of OCN + early CEPC tend to be linked to the risk of all-cause mortality.